Professional Personal Competencies Pediatrician - M. G. Romantsov; O. V. Shamsheva; I. Y. Melnikova (Детские инфекции (Москва))
Conceptual position of vocational education is the personal and professional development learning and personal development is an essential goal of vocational education. The formation and development of the specialist involves the development of a professional intelligence, independence, self-confidence, professionally important qualities and competence.